Patient Satisfaction among Different Age Groups Who Underwent Aesthetic and Functional Rhinoplasty in Sulaymaniyah - S Sabir, Saman; A Hawrami, Falah; M Amin , Zanyar (Diyala Journal of Medicine, 2022)
Background: Cosmetic surgery is performed to improve an individual’s satisfaction with their appearance and to improve their psychological health by improving self-confidence. Our study aimed to evaluate patient satisfaction regarding nose appearance and function. Objective: To evaluate the satisfaction of patients who underwent rhinoplasty by using the Rhinoplasty outcomes evaluation (ROE) questionnaire and to determine the impact of patient age on the outcomes. Patients and Methods: A prospective study of 90 patients who underwent open rhinoplasty procedures, including other nasal procedures like septoplasty or turbinoplasty, in both private and public Sulaimani Surgical Teaching Hospitals (department of oral maxillofacial surgery) from October 2020 to March 2022. The Rhinoplasty Outcomes Evaluation (ROE) questionnaire was used for esthetic and functional assessment. Results before and after surgery were compared. Results: In this study, ninety patients participated by completing the questionnaires and the follow-up period six months postoperatively. The main reasons for rhinoplasty in our patients were: esthetic 50% (n=45), functional 8.9 % (n=8), and a combination of both esthetic and functional in 41.1% (n=37) of patients. There was a significant overall increase in patient satisfaction with functional and esthetic outcomes post-surgery (p < 0.01), and there was no significant difference among different age groups postoperatively (p > 0.01) based on ROE. Conclusion: There was a significant overall increase in patients’ satisfaction with functional and aesthetic outcomes post-surgery. There was no significant difference in satisfaction among different age groups.